1971
DOI: 10.1111/j.1755-3768.1971.tb02968.x
|View full text |Cite
|
Sign up to set email alerts
|

On Repeated Tonometry

Abstract: The fact that repeated tonometry is associated with an apparent fall in intraocular pressure was first noted by Stocker 1958 and Goldmann 1958. Since then it has been strongly confirmed (Moses 1961, Bechrakis 1966 and there is full agreement on the following points:1. When the measurements are repeated every minute there is a fall of 3-4 mm Hg in 5 minutes and about 5 mm Hg in 12 minutes. According to Bechrakis the fall is exponential. On the contralateral eye there is a sympathetic pressure fall.2. The declin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
1
1

Year Published

1973
1973
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(34 citation statements)
references
References 7 publications
1
31
1
1
Order By: Relevance
“…Moreover, many investigators have reported problems with IOP values decreasing during successive measurements using applanation tonometers . Repeated applanation IOP measurements in humans may iatrogenically alter the measured IOP value, with both linear and exponential changes reported . Whitacre et al .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many investigators have reported problems with IOP values decreasing during successive measurements using applanation tonometers . Repeated applanation IOP measurements in humans may iatrogenically alter the measured IOP value, with both linear and exponential changes reported . Whitacre et al .…”
Section: Discussionmentioning
confidence: 99%
“…IOP decreases when it is measured consecutively with various tonometers, as in the case of IOP measurements by GAT, a phenomenon that was first pointed out during the development of the tonometer 2,20. Significant IOP-lowering effects as a result of consecutive measurements are not seen with Icare, or are less than those associated with consecutive measurements using a GAT 21.…”
Section: Discussionmentioning
confidence: 99%
“…Goldmann applanation tonometer measurements were performed after use of the noncontact tonometer to eliminate the reported possible effect of ocular massage by the Goldmann applanation tonometer 20. In the second measurement session, except for randomization, the order of use of the instruments and the eye assessed was the same as in session 1.…”
Section: Methodsmentioning
confidence: 99%